Advanced fractionation methods for the microstructure analysis of complex polymers1. (12th March 2015) - Pasch, Harald; Domb, Abraham; Slomkowski, Stanislaw
<x xml:space="preserve">Abstract</x> This review discusses some recent work on the microstructure analysis of complex polymers using advanced fractionation methods. Complex polymers are distributed in a number of molecular parameters including molar mass, chemical composition, molecular architecture, and microstructure. Molar mass and chemical composition analysis is typically conducted by a range of spectroscopic and chromatographic methods, size exclusion chromatography and high‐performance liquid chromatography (HPLC) being the most important fractionation methods. It is shown that HPLC is also very sensitive regarding polymer microstructure and can be used for the fractionation of e.g. polymethacrylates, polyisoprene, and polybutadiene. The best approach to the quantitative analysis of microstructure distributions is the on‐line coupling of the fractionation with 1H nuclear magnetic resonance spectroscopy. The spectroscopic analysis of chromatographic fractions provides concentration profiles of the tactic units as a function of the chromatographic separation and can be used for both HPLC and size exclusion chromatography. Apart from column‐based fractionations, channel‐based fractionations such as thermal field flow fractionation are powerful tools for microstructure analysis of complex polymers. It has been shown very recently that thermal field flow fractionation is capable of fractionating polyisoprene and polybutadiene according to microstructure. Copyright © 2015 John Wiley & Sons, Ltd.